(untitled) (Journal of the College of Basic Education, 2023)
Andalusia remained throughout the Arab rule, which took a long time, which took more than eight centuriesWhich constitutes a model of tolerance and coexistence between peoples and races, including Arabs, Muzaldin, Arabists and Jewssqalba; And other sects that came from different parts of the world to melt into a unitSocial characterized by common cultural characteristics and remarkable social harmony, despite what was appearingSometimes religious fanaticism, which was nothing but exceptions in the history of the Islamic state inAndalus.